Fractionation and mobility of thallium in areas impacted by mining-metallurgical activities: Identification of a water-soluble Tl(I) fraction. (June 2018) - Cruz-Hernández, Yusniel; Ruiz-García, Mismel; Villalobos, Mario; Romero, Francisco Martin; Meza-Figueroa, Diana; Garrido, Fernando; Hernández-Alvarez, Elizabeth; Pi-Puig, Teresa
Abstract: Mining and metallurgy generate residues that may contain thallium (Tl), a highly toxic metal, for which it is currently not feasible to determine its geochemical speciation through X-ray absorption spectroscopy due to a combination of very low contents and the interference of accompanying high arsenic contents. Therefore, fractionation studies in residues and soils are required to analyze the mobility and bioavailability of this metal, which in turn provide information to infer its speciation. For this purpose, in this work a modification of the BCR procedure was applied to residues and contaminated soils from three mining zones of Mexico and two mining zones of Spain, spanning samples with acidic to alkaline pH values. The Tl extraction procedure consisted of the following fractions: (1) water-extractable, (2) easily exchangeable and associated to carbonates, associated to (3) poorly-crystalline and (4) crystalline Fe and Mn oxyhydroxides, and (5) associated to organic matter and sulfides; and finally a residual fraction as associated to refractory primary and other secondary minerals. The extracted contents were analyzed by Inductively-Coupled Plasma with Mass Spectrometry. Surprisingly, water-soluble, in Tl(I) oxidation state, was detected in most areas, regardless of the pH, a fact that has not been reported before in these environments, and alerts to potential health risks not previously identified. Most of the samples from a metallurgy area showed high levels of Tl in non-residual fractions and a strong correlation was obtained between extracted Mn and Tl in the third fraction, suggesting its association to poorly crystalline manganese oxides. In the majority of samples from purely mining environments, most of the Tl was found in the residual fraction, most probably bound to alumino-silicate minerals. The remaining Tl fractions were extracted mainly associated to the reducible mineral fractions, and in one case also in the oxidizable fraction (presumably associated to sulfides). Capsule: Soluble Tl(I) was found in all soil samples contaminated with either mining or metallurgical wastes. Additionally, in those affected by metallurgical wastes a very strong Tl-Mn correlation was found. Graphical abstract: Image 1 Highlights: Tl fractionation and mobility were investigated, and its geochemical speciation was inferred in five mining-impacted areas. Significant contents of Tl(I) were found in the water-soluble fraction of all areas. The water-soluble Tl(I) may impact either aquatic or eolian environments. In most of the metallurgical area samples a strong retention of Tl(III) by Mn oxides is inferred. In mining environments Tl was mostly found in the residual fraction, but non-negligible Tl was found in more mobile fractions.